2010
DOI: 10.1590/s0103-64402010000500004
|View full text |Cite
|
Sign up to set email alerts
|

Use of graduated syringes for measuring salivary flow rate: a pilot study

Abstract: The evaluation of the salivary flow rate is important in several situations of dental practice. However, weighing the collected salivary volume it is not a practical method in public health services. This work evaluated the use of hypodermic graduated syringes as a simpler alternative method to measure the salivary flow rate. Saliva samples were obtained from 50 individuals (31 females and 19 males) aged 8 to 32 years (mean age: 12.4 years), recruited at the outpatient dental clinics of two public health cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 15 publications
1
16
1
4
Order By: Relevance
“…This may have a negative impact for specific patients as a flow rate of <0.1 ml unstimulated saliva is the cut-off for receiving subsidized dental care in countries such as Norway and Sweden. Our results are in contrast to a recent study of Alves et al [4] where it is suggested that volume measurement of saliva in graduated syringes is comparable to that of weight measurement. It is noteworthy that the aforementioned study comprised healthy individuals; medically compromised patients were excluded which could explain the divergent results.…”
Section: Groupcontrasting
confidence: 99%
See 1 more Smart Citation
“…This may have a negative impact for specific patients as a flow rate of <0.1 ml unstimulated saliva is the cut-off for receiving subsidized dental care in countries such as Norway and Sweden. Our results are in contrast to a recent study of Alves et al [4] where it is suggested that volume measurement of saliva in graduated syringes is comparable to that of weight measurement. It is noteworthy that the aforementioned study comprised healthy individuals; medically compromised patients were excluded which could explain the divergent results.…”
Section: Groupcontrasting
confidence: 99%
“…This is a relatively simple and non-invasive method recommended by the Swedish Social Insurance Board [3]. In other countries, different methods, for example weighting of saliva, may be more common [4].…”
Section: Introductionmentioning
confidence: 99%
“…6 Individu dengan laju aliran saliva yang rendah akan mengalami masalah medis seperti xerostomia, mucosal inflammation, burning mouth, gangguan pengecapan, demineralisasi gigi, kesulitan pengunyahan, gangguan bicara dan retensi gigi tiruan yang buruk. 7 Laju aliran saliva yang rendah juga mempengaruhi dietary habit dan status gizi sehingga berakibat negatif terhadap kualitas hidup individu. Laju aliran saliva dipengaruhi oleh banyak faktor, salah satunya adalah status gizi.…”
Section: Pendahuluanunclassified
“…7 Laju aliran saliva dipengaruhi oleh banyak faktor, salah satunya adalah status gizi. Status gizi yang tidak normal dapat mempengaruhi sekresi dan komposisi saliva sehingga menyebabkan laju aliran saliva berkurang.…”
Section: Pembahasanunclassified
“…To reduce the effect of circadian rhythms, all saliva samples were collected within the same period of time on every data collection day between 8:00 am and 10:00am. Unstimulated saliva was collected using the spit method (Navazesh, 1993;Alves, 2010;Beltzer, Fortunato et al, 2010) over a period of five minutes when the participants were comfortably seated on a dental chair. The flow rate was then calculated by using grams per minute (g/min).…”
Section: Saliva Collection and Determination Of Salivary Flow Ratementioning
confidence: 99%